Development and Validation of Gene-Based SSR Markers in the Genus Mesembryanthemum - Muhanad Akash; Safwan Shiyab; Mohammed Saleh; Shireen M. Hasan; Mahmoud AbuHussein; Wajdy Al-Awaida (Scientifica)
Bioinformatics tools have been employed for the direct development of gene-based simple sequence repeat (SSR) markers. Through the analysis of 28,056 Mesembryanthemum expressed sequence tag (EST) sequences, a total of 5,851 ESTs containing SSRs were identified, amounting to approximately 17.07 Mb. Among these, 938 EST sequences harbored more than one SSR marker, and 788 EST-SSR sequences were found in compound form. The most prevalent types of SSR motifs were mononucleotide repeats (MNRs), accounting for 44%, followed by di-nucleotide repeats (DNRs) at 37%, and trinucleotide repeats (TNRs) at 16%. Notably, TNR or longer SSR motifs primarily consisted of shorter repeat lengths, with only 51 motifs containing 10 or more repeats. The BLASTX analysis successfully assigned functions to 4,623 (79%) of the EST sequences. Among the developed primer sets, 21 primers amplified a total of 65 alleles, with primer PMA79 EST-SSR exhibiting the maximum of six alleles. The polymorphic information content (PIC) values ranged from 0 to 0.76, with a mean of 0.47. The marker index (MI) and discriminating power (D) values reached 0.66 (primer PMA63) and 0.95 (primer PMA20), respectively. Utilizing the unweighted pair group method with arithmetic mean (UPGMA), a dendrogram was constructed, successfully segregating the 24 Mesembryanthemum genotypes into three distinct clusters, with a similarity coefficient ranging from 0.96 to 0.38. In this study, we have developed a total of 83 EST-SSR primer pairs specific to the Mesembryanthemum genus. These newly developed EST-SSRs will serve as valuable tools for researchers, particularly molecular breeders, enabling gene-based identification and trait selection through marker-assisted breeding approaches.